(3GdbUjOI GdMQHGhjIs - (3YKeGf Hf YjSi Hf efUhQ GdHdWj, JGL GdOjf CHh GdaJM,J (B599 (3g` s
(3ChdgG (B:s
(3Gfi GeQGA dGjWHfj hbGd SjHhjg gh eKd bhdge GdMUf GdhLg aGQbJ TQI YjTj GPG aGQbJfi hGdZQGe s
(3BNQgG (B:s
(3Gfi hOOJ hbO SFeJ GdYjT dh jOfhG GLeGe hGddg GYde fLRJ GdbUjOI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B248 - (3U(B249s
(3GfXQg eY GdeNWhW Qbe (B292 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1337s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdfMhs